Detection of Candida tropicalis from camel mastitis - S. A. Esmaeel; S. F. H. Al-Abedi; M. A. Altaliby; Q. T. Al-Obaidi (Bulgarian Journal of Veterinary Medicine)
The present study was conducted to detect Candida tropicalis as a cause of camel mastitis (CM) us-ing routine diagnostic tests including Sabouraud’s dextrose agar (SDA) and API (analytical profile index) test strips, which were confirmed through amplification of the 18S rRNA gene of C. tropicalis using conventional polymerase chain reaction (c-PCR) technique and to investigate of the virulence genes of C. tropicalis including secreted aspartyl proteinase (SAPT4) and agglutinin-like sequence (ALST1) genes using c-PCR. Between January 2023 and May 2023, seventy mastitis milk samples were obtained from camels in Wasit province, Iraq. Results indicated that C. tropicalis was identified in 15/70 (21.4%) and 10/15 (66.6%) of mastitis milk samples based on milk cultured in SDA and API 20C AUX, respectively. The positive samples for C. tropicalis were 15/15 (100%) via the c-PCR technique. The results also showed that C. tropicalis positive for virulence genes SAPT4 and ALST1 in camel mastitis samples were 12/15 (80%) and 10/15 (66.6%), respectively. This study concluded that C. tropicalis in camels is the most common cause of mycotic mastitis in Wasit province, Iraq. The presence of virulence factors ALST1 and SAPT genes of C. tropicalis in camel milk samples could be considered as transmission vehicle of these pathogens.